Beyond the Border: Yellow Goes International. (October 2016) - Ahmed, Jashim Uddin; Rifat, Afrin; Nisha, Nabila; Manirujjaman, Md; Shrensky, Ruth
This article reports a case study on the Bangladeshi leading fashion brand Yellow. The study investigated Yellow's international marketing process, following the brand's journey from Bangladesh to Pakistan and South Korea. Conducting desk research and interviewing corporate personnel from Yellow, this case study obtained in-depth information and broader understanding about the internationalization of Yellow. The article investigated Yellow's reasons for going international, how it chose its international markets and market segments and the challenges Yellow faced on its journey. The article is divided two parts: the first part discusses Yellow's local expansion and the second part discusses Yellow's internationalization.